Cummins, Inc. : on the road or in the lab? Meeting new emission standards in China (C) - Bagley, Constance E.; Rae, Douglas W.; Rosenthal, Jean W., 1945- (London : Yale School of Management, 2010)
By July 1, 2008, all of China's diesel engine manufacturers would be offering products that met the new NS-III emissions standard. But as the standard went into effect, Steve Chapman, Group Vice President -- Emerging Markets and Businesses for Cummins, Inc., faced a new dilemma. One competitor was proposing a design that would create havoc in the market.
Originally published in Bagley, C., Rae, D., & Rosenthal, J. (2010). Cummins, Inc.: On the road or in the lab? Meeting new emission standards in China (C). 10-019. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Cummins, Inc; Internal combustion engine industry -- Environmental aspects -- China; Air quality -- Standards -- China; Competition -- China